2016
DOI: 10.1259/dmfr.20150129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of display type, DICOM calibration and room illuminance in bitewing radiographs

Abstract: DICOM calibration improves the detection of enamel and dentinal caries in bitewing radiographs, particularly in bright lighting. Therefore, a calibrated consumer grade display can be recommended as a diagnostic tool for viewing bitewing radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
“…DICOM-calibrated consumer grade display is significantly better than uncalibrated consumer grade display, slightly better than tablet and almost equal to medical displays in the interpretation of enamel and dentinal caries in bitewing radiographs. 23 The lighting conditions in the practice have an influence on caries perception as well. 13 It is remarkable that resolution and diameter are the key factors when buying a display, while standard consumer displays are less accurate than DICOM calibrated displays.…”
Section: Use Of Calibrated Monitorsmentioning
confidence: 99%
“…Nevertheless, consumer-grade displays cannot be integrated into clinical practice as high standards have to be fulfilled to be accepted as a medical application (16). Because medical-grade displays are expensive and high-quality consumer-grade displays are widely available and may provide comparable image quality and diagnostic accuracy, several software packages have become available for effective grayscale calibration of consumer-grade displays (3,4,8).…”
Section: Introductionmentioning
confidence: 99%
“…First, a medical-grade workstation, which fulfils the special requirements for medical use, should be used by the radiologist providing teleradiology services and therefore should be available at his or her home, which is sometimes not possible (3). Several non-medical displays have already been investigated in terms of their suitability for radiological applications (3)(4)(5)(6)(7)(8). Second, transmission of large amounts of data is necessary when sending sets of images, e.g.…”
Section: Introductionmentioning
confidence: 99%